Final 50 Feet of the Urban Goods Delivery System: Pilot Test of an Innovative Improvement Strategy - Goodchild, Anne; Kim, Haena; Ivanov, Barbara (My University, 2019)
The “Final 50 Feet of the Urban Goods Delivery System: Pilot Testing Innovative Improvement Strategies” project will provide new data-based knowledge and insights about the effects of truck parking strategies proposed in the City of Seattle, before they are broadly implemented. Goals of the project are reduction in dwell time, the time a truck is parked in a load/unload space. There are both public and private benefits to reaching this goal. As well as a reduction in failed first deliveries. Several Urban Freight Lab members told the research team that 8-10% of first delivery attempts in urban areas across the country fail. A study conducted in the UK reported that the cost of failed first deliveries was 771 billion euros in 2014.
data link: https://doi.org/10.7910/DVN/UHYGAW
Keywords: Urban Freight Delivery